Solid Waste Management in India: A Review and Road Rhead - Artee Aggrawal; Gunchita Kaur Wadhwa (Journal of International Conference Proceedings (JICP), 2018)
This study involves in depth research in the various aspects of the solid waste management which includes studying waste generation its classification and further focusing mainly on solid waste. The management of the waste has been an issue for every country as the increase in population has also led to the increase in the waste generation. Managing of this waste has been an issue of concern for all the countries across the globe. Out of the many sorts solid waste is one of the major contributors in the category of wastes and managing it is a task. This study presents a comprehensive review of literature of solid waste management and best practices adopted in various countries for the issue. The paper also discusses at length strategy implemented in various parts of India keeping in mind the diversity and a variety of factors. Additionally, the existing legislations and norms were studied according to which the areas of improvements and the future scope are suggested. Keywords: Solid waste, management, legislations.